Penerapan Pendekatan Arsitektur Kontemporer pada Bangunan Pusat Kajian Islam di Kota Makassar - Pratiwi, Nurazizah; Rahayu, Irma; Nursyam, Nursyam (TIMPALAJA : Architecture Student Journals, 2025)
Contemporary architecture emerged as a response to changing times that demand innovation in architectural form and concept. This shift is driven by architects’ dissatisfaction with rigid conventional architectural theories. Dynamic design adaptations—such as the use of curved exterior lines, unique asymmetrical room shapes, aesthetically placed large windows, the application of neutral and bold colors, and unconventional materials like glass and metal—characterize contemporary architecture. Additionally, buildings often feature open roofs that apply environmentally friendly principles while providing protection from sunlight. To ensure that Islamic buildings remain relevant and modern in line with current developments, this study employed methods including literature review, analysis of contemporary design, and the application of aesthetic principles along with environmentally sustainable functions in the design process. The results demonstrate that the Islamic Studies Centre can achieve modern, aesthetic, and functional buildings through a contemporary architectural approach without compromising Islamic values while also supporting sustainability and user comfort.